Ehrenfest’s Theorem revisited - Arodź, Henryk Stanisław (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2019)
Historically, Ehrenfest’s theorem (1927) is the first one which shows that classical physics can emerge from quantum physics as a kind of approximation. We recall the theorem in its original form, and we highlight its generalizations to the relativistic Dirac particle and to a particle with spin and izospin. We argue that apparent classicality of the macroscopic world can probably be explained within the framework of standard quantum mechanics.